On the linear stability of the extreme Kerr black hole under axially symmetric perturbations - Dain, Sergio Alejandro (2014)
We prove that for axially symmetric linear gravitational perturbations of the extreme Kerr black hole, there exists a positive definite and conserved energy. This provides a basic criteria for linear stability in axial symmetry. In the particular case of Minkowski, using this energy we also prove the pointwise boundedness of the perturbation in a remarkably simple way.